Piazze Verdi. Spazio pubblico materiale e immateriale nella città italiana - Magnier, Annick (SocietàMutamentoPolitica, 2019)
Which functions, in the “Information Age”, can maintain the “Piazza”, the traditional locus of encounter and debate in the European Mediterranean city? The renewed vividness of the reactive movements against public projects of regeneration of squares in different Italian cities could be interpreted as a signal of a persisting strong link between public realm and urban public space. Starting from the exemplary intensely mediatized case of the restyling of Piazza Verdi in La Spezia, this article leads on the contrary to emphasize a recent involution in the national debate on urban public spaces; and proposes lines of analysis for an empirical assessment of the efficacy of these spaces in sustaining today civicness and right to the city.